Documentary Film Based History Learning Media Material on the Japanese Occupation in Pontianak - Yafi, Reyhan; Aria Yuliantri, Rhoma (LPPM Undiksha, 2024)
History teachers in senior high schools need variations in the use of learning media in the classroom. This research aims to design history learning media based on documentary films of Japanese occupation and analyze the feasibility of the product. The methodology used was research and Development (R&D) with the ADDIE model. The subjects involved in the research consisted of the head of curriculum, history teachers, and students. The data collection methods used were observation, interview, and assessment questionnaires. Then, the data analysis used was qualitative and quantitative. The validation results include material expert validation getting a good category and media expert validation getting a good category. While the teacher's assessment got a good category, the assessment of students in the small group trial got a good category, and the large group trial got a good category. This finding shows that the history learning media based on the documentary film of the Japanese Occupation is feasible to use in learning history. Therefore, this media is the main alternative in providing variations in the use of learning media in the classroom.